Impressive clinical response following combined BRAF and MEK inhibition in a low-grade serous ovarian carcinoma patient with a BRAF V600E mutation - Rodzajewska, Anna; Kuryło, Weronika; Szklener, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Low-grade serous ovarian cancer (LGSOC) accounting for less than 10% of all serous ovary cancers. The chemoresistance inherent to this type of ovarian cancer narrows the therapeutic options, especially in the recurrent setting. It is thought that the mitogen-activated protein kinase (MAPK) pathway plays a significant role in the pathogenesis of these tumours, and about 2 to 20% of LGSOC harbour a BRAF mutation. Case report: We present a case report of a 58-year-old woman with LGSOC FIGO stage IIIC who presented recurrence of the tumor process after total abdominal hysterectomy and systemic treatment. Thereafter, she underwent molecular profiling, which revealed a BRAF V600E mutation; accordingly, the patient was administered dabrafenib and trametinib combination therapy. The patient noted significant clinical improvement with normalization of CA 125 and radiological partial response. To date, the patient still maintains partial response, with good treatment tolerance and performance status ECOG 0/1 and good quality of life. Conclusions: LGSOC represents the challenge that is managing a rare cancer with scarce therapeutic options. Given the prevalence of BRAF mutations in this type of tumour, it might be relevant to consider genetic testing. It may provide new treatment opportunities for patients with a known chemoresistant tumour, by identifying potential actionable targets and avoid potential toxicities associated with chemotherapy. Here we demonstrate that impressive clinical responses can be achieved in BRAF mutated LGSOC treated with combined BRAF and MEK inhibitor treatment.